Some generalized Hermite-Hadamardtype integral inequalities for generalizeds-convex functions on fractal sets - Kilicman, Adem; Saleh, Wedad (SpringerOpen, 2015)
In this article, some new integral inequalities of generalized Hermite-Hadamard type for generalized s-convex functions in the second sense on fractal sets have been established.